Kurkumin Meningkatkan Sensitivitas Sel Kanker Payudara terhadap Tamoksifen melalui Penghambatan Ekspresi P-glikoprotein dan Breast Cancer Resistance Protein - Sianipar, Erlia Anggrainy; Louisa, Melva; Wanandi, Septelia Inawati (Jurnal Farmasi Indonesia, 2017)
Background:The decreased of sensitivity or resistance to tamoxifen occured after long-term treatment in breast cancer. One of the major factor in tamoxifen resistance is over expression of efflux transporter P-glycoprotein (P-gp) and Breast Cancer Resistance Protein (BCRP). Curcumin has known as inhibitor of P-gp and BCRP. The addition of curcumin to the tamoxifen resistant cells is expected to increase the sensitivity of breast cancer cells to tamoxifen. Method:MCF-7 breast cancer cell linewas induced with tamoxifen 1 uM for 10 passage (MCF-7(T)), then cell viability and mRNA expression of P-gp and BCRP were analyzed. To the MCF- 7(T) cells, curcumin was given at of 5/10/20 uM with or without tamoxifen for 5 days and cell viability and mRNA expression of P-gp and BCRP were analyzed on day 5. As positive control, verapamil 50 uM was used as P-gp inhibitor, ritonavir 15 yM and nelfinavir 15 yM were used as BCRP inhibitor. Result:MCF-7(T) cells sensitivity to tamoxifen has decreased with 11,8 times reduction in sensitivity towards tamoxifen, the increased of cell viability, and mRNA expression of P-gp and BCRP mRNA increased 10,82 and 4,04 fold respectively in MCF-7(T) cells. Then after administration of curcumin with or without tamoxifenfor5 days then the cell viability and the mRNA expression of P-gp mRNA and BCRP decreased. Conclusion:Curcumin iIncreased the sensitivity of MCF-7(T) to tamoxifen, characterized by the decreased of cell viability and mRNA expression of P-gp and BCRP. But the administration of combination curcumin with tamoxifen was more potent than curcumin alone. The iIncreased sensitivity was estimated at least in part through the inhibition of P-gp and BCRP MRNA expression by curcumin. Background:The decreased of sensitivity or resistance to tamoxifen occured after long-term treatment in breast cancer. One of the major factor in tamoxifen resistance is over expression of efflux transporter P-glycoprotein (P-gp) and Breast Cancer Resistance Protein (BCRP). Curcumin has known as inhibitor of P-gp and BCRP. The addition of curcumin to the tamoxifen resistant cells is expected to increase the sensitivity of breast cancer cells to tamoxifen. Method:MCF-7 breast cancer cell linewas induced with tamoxifen 1 uM for 10 passage (MCF-7(T)), then cell viability and mRNA expression of P-gp and BCRP were analyzed. To the MCF- 7(T) cells, curcumin was given at of 5/10/20 uM with or without tamoxifen for 5 days and cell viability and mRNA expression of P-gp and BCRP were analyzed on day 5. As positive control, verapamil 50 uM was used as P-gp inhibitor, ritonavir 15 yM and nelfinavir 15 yM were used as BCRP inhibitor. Result:MCF-7(T) cells sensitivity to tamoxifen has decreased with 11,8 times reduction in sensitivity towards tamoxifen, the increased of cell viability, and mRNA expression of P-gp and BCRP mRNA increased 10,82 and 4,04 fold respectively in MCF-7(T) cells. Then after administration of curcumin with or without tamoxifenfor5 days then the cell viability and the mRNA expression of P-gp mRNA and BCRP decreased. Conclusion:Curcumin iIncreased the sensitivity of MCF-7(T) to tamoxifen, characterized by the decreased of cell viability and mRNA expression of P-gp and BCRP. But the administration of combination curcumin with tamoxifen was more potent than curcumin alone. The iIncreased sensitivity was estimated at least in part through the inhibition of P-gp and BCRP MRNA expression by curcumin.